Mobilitas Tenaga Kerja Dan Dampaknya Terhadap Kehidupan Sosial Budaya Pada Masyarakat Perdesaan - Rahman, Abdul (Research Agency for Humanity and Urban, 2023)
Limited job opportunities are a national issue and from year to year the number of unemployed is increasing. One of the causes of the lack of employment is the unequal number of the labor force compared to the available job opportunities. On the one hand, the labor force, especially the young labor force, tends to be disinterested in working in rural areas. This study aims to analyze the structure of the workforce, employment opportunities and labor mobility in rural areas. The approach used in this study is a case study in Bulutellue Village, Bulupoddo District, Sinjai. Data collection was carried out in participatory group discussions. Limited job opportunities and low wage rates in rural areas caused workers to migrate out of the region, with the aim of migrating outside the region and also abroad. The workforce potential is quite high but the quality of the workforce is still low. Efforts to increase labor resources and create job opportunities that lead to the development of the informal economic sector are urgently needed to accelerate rural development and reduce labor migration.